Struktur Kalimat dalam Kolom Kriminal pada Harian Digital “Jawa Pos” - Aldila Julistina Eraku; Supriyadi Supriyadi; Ulfa Zakaria (Journal on Education, 2024)
The aim of this research is to find out the sentence structure in the crime column in the digital daily Jawa Pos. Based on this, the population for this study is the sentences contained in the content of news that have been classified in the crime column of the digital daily Jawa Pos that have been found. The method in this research is a descriptive approach with a qualitative research type. The data collection technique in this research is a document technique. Data analysis techniques in research useChaer's (2015) theory regarding sentence structure which is analyzed based on the function of the sentence. The results of the research show that the sentences contained in the Jawa Pos digital daily news regarding crime in 8 news stories were found to be incomplete sentences and complete sentences, as well as direct and indirect sentences, with the function positions SPO, SPK, SPOK, SPOPel, SPOPelK, SPPel, SPPelK , SP, SOK, POK, SK, PK, SO, K, and O. Based on these results it was found149 sentences, with 126 complete sentences and 23 incomplete sentences. Then 24 direct sentences and 125 indirect sentences were found.